On the othogonal trajectories and conformal mapping of complex variable functions - Kus Prihantoso Krisnawan; Atmini Dhoruri (Jurnal Sains Dasar, 2014)
This research goal is to investigate the connection of orthogonal trajectories, analitic functions, and conformal mapping. Orthogonal trajectories are the intersection of two families of mutually perpendicular curves. The analytical property of a complex function f(z) = u + iv is investigated using Cauchy-Riemann conditions and then the geometric shapes of u and v are interpreted. The results showed that if two functions are mutually harmonic conjugate, then they are mutually orthogonal trajectories. If two families of curves of mutually orthogonal trajectories are mapped by conformal mapping then the result functions are also mutually orthogonal trajectories.Key words: orthogonal trajectories, analytic functions, conformal mapping